Response requirements modulate tactile spatial congruency effects. - Gallace, A; Soto-Faraco, S; Dalton, P; Kreukniet, B; Spence, C (2008)
Several recent studies have provided support for the view that tactile stimuli/events are remapped into an abstract spatial frame of reference beyond the initial somatotopic representation present in the primary somatosensory cortex. Here, we demonstrate for the first time that the extent to which this remapping of tactile stimuli takes place is dependent upon the particular demands imposed by the task that participants have to perform. Participants in the present study responded to either the elevation (up vs. down) or to the anatomical location (finger vs. thumb) of vibrotactile targets presented to one hand, while trying to ignore distractors presented simultaneously to the other hand. The magnitude and direction of the target-distractor congruency effect was measured as participants adopted one of two different postures with each hand (palm-up or palm-down). When the participants used footpedal responses (toe vs. heel; Experiment 1), congruency effects were determined by the relative elevation of the stimuli in external coordinates (same vs. different elevation), regardless of whether the relevant response feature was defined externally or anatomically. Even when participants responded verbally (Experiment 2), the influence of the relative elevation of the stimuli in external space, albeit attenuated, was still observed. However, when the task involved responding with the stimulated finger (four-alternative forced choice; Experiment 3), congruency effects were virtually eliminated. These findings support the view that tactile events can be remapped according to an abstract frame of reference resulting from multisensory integration, but that the frame of reference that is used while performing a particular task may depend to a large extent on the nature of the task demands.